Study of cutting force and surface roughness on drilling stainless steel 316L under various coolant condition - Kamdani, K.; Hamsah, A.A.; Rafai, N.H.; Rahim, M.Z.; Wong, C.K.; Chong, Y. L. (Trans Tech Publications, 2018)
Drilling is the metal cutting process that are widely used in industrial sector such as in aerospace, automotive and manufacturing to produce a various of durable parts. Stainless steels in general are regarded as difficult to machine materials due to their high tendency to work harden; their toughness and relatively low thermal conductivity. In this research, the experimental setup for the effect of various parameters on drill performance in term of cutting force and surface roughness. Stainless steel 316L used as workpiece and uncoated tungsten carbide drill bit as the tool. From the experimental investigation, the results show that internal coolant with helix angle of 40 and feed rate of 0.1 mm/rev condition is the best drilling condition in term of thrust force and surface roughness. By observation on experiment, MQL coolant condition give highest thrust force while internal coolant is best condition to have most minimum force. For internal coolant, MQL and external supply, the optimum helix angle to obtain low surface roughness is 15° and 40°.